Developing creative skills of pre-school children from the perspective of intellectual factors of creativity - Oana Iuliana ENACHE (ACROSS)
The human psychic system is based on complex psychological processes and functions, in which activities and psychic attributes that form personality are integrated. The personality system is studied under the aspect of temperament, aptitudes and character, besides which, an important place is occupied by creativity, a term emphasized in relation to its three meanings creative behavior and psychic activity, personality structure or creative style and group creativity, all of which are relevant from the point of view of the individual's adaptation to the environment in which he lives. This complex approach needs to be started at the earliest possible stage, so that educational actions can make their mark on individual typology or in certain contexts of performance achieved as a result of group activity.